2017
DOI: 10.3390/beverages3040059
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Characterization of Apple Nectars Supplemented with Araçá-boi (Eugenia stipitata Mac Vaugh—Myrtaceae)

Abstract: Fruits and vegetables are known as sources of nutritionally important phytochemicals, such as phenolic compounds, and Brazilian biodiversity may be hiding many underexplored fruits with potential health benefits. In this study, we formulated a fruit-based beverage by supplementing known amounts of freeze-dried araçá-boi (Eugenia stipitata) (FD) to a commercial apple nectar in order to evaluate the impact in terms of nutritional (level of phenolic compounds, flavonoids and antioxidant capacity) and sensory para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Further, mixing of spice extract might be the additional advantage to improve the overall phenolic content of S3 nectar. Baldini et al (2017) observed a similar trend of increase in the resulting values of phenolics in apple nectar when supplemented with freeze-dried Araçá-boi. Resulting values illustrated in Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Further, mixing of spice extract might be the additional advantage to improve the overall phenolic content of S3 nectar. Baldini et al (2017) observed a similar trend of increase in the resulting values of phenolics in apple nectar when supplemented with freeze-dried Araçá-boi. Resulting values illustrated in Fig.…”
Section: Resultssupporting
confidence: 64%
“…Further, vegetables and fruits are considered as an excellent means of delivering bioactive compounds. Thus, the beverage industry isfocusing on blending the nutritionally rich medicinal vegetables with fruit juices to improve the overall functional and flavor profile (Baldini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto apesar de todas essas propriedades o araçá-boi ainda apresenta uma perecibilidade alta, dificultando principalmente a logística no que diz respeito a sua comercialização, além de apresentar poucos estudos relacionados a sua caracterização físico-química e sensibilidade microbiologia o que dificulta ainda mais o conhecimento abrangente de suas características de conservação (Baldini et al, 2017). Com isso faz-se necessário a busca de tecnologias de conservação para manutenção das propriedades funcionais e nutricionais, possibilitando o alcance de novos mercados.…”
Section: Introductionunclassified
“…All over the world, there are traditional non-dairy bev-erages produced by hand that is based on PBDS and, in some cases, fruit juices and nectars. [27][28][29][30] In beverages, fermentation can occur spontaneously (due to the presence of microorganisms from the raw material itself ) or controlled (by the addition of selected microorganisms). For large-scale production, spontaneous fermentation is not attractive due to the high risk of contamination, which compromises the shelf life of the product and the availability of safe food.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…All over the world, there are traditional non-dairy beverages produced by hand that is based on PBDS and, in some cases, fruit juices and nectars. 27–30…”
Section: Probiotics Prebiotics Symbiotics Parabiotics Postbiotics And...mentioning
confidence: 99%